The lncRNA BORG Drives Breast Cancer Metastasis and Disease Recurrence. Issue 1 (December 2017) - Gooding, Alex; Zhang, Bing; Jahanbani, Fereshteh; Gilmore, Hannah; Chang, Jenny; Valadkhan, Saba; Schiemann, William
Abstract Long noncoding RNAs (lncRNAs) have emerged as potent regulators of breast cancer development and progression, including the metastatic spread of disease. Throughin silico and biological analyses, we identified a novel lncRNA, B MP/O P-R esponsiveG ene (BORG), whose expression directly correlates with aggressive breast cancer phenotypes, as well as with metastatic competence and disease recurrence in multiple clinical cohorts. Mechanistically, BORG elicits the metastatic outgrowth of latent breast cancer cells by promoting the localization and transcriptional repressive activity of TRIM28, which binds BORG and induces substantial alterations in carcinoma proliferation and survival. Moreover, inhibiting BORG expression in metastatic breast cancer cells impedes their metastatic colonization of the lungs of mice, implying that BORG acts as a novel driver of the genetic and epigenetic alterations that underlie the acquisition of metastatic and recurrent phenotypes by breast cancer cells.